PROFILE OF PRACTITIONERS OF PHYSICAL ACTIVITIES OF THE ACADEMY OF THE CITY OF SQUARE MACAPÁ (Fiep Bulletin - online, 2016)
The present study aimed to profile the fitness enthusiasts of Academy Square Garden Happiness Macapá- AP. For this, we used a questionnaire with close to getting information on gender, age, motivation and socioeconomic profile of practicing questions. 46 individuals, 38 females and 8 males with a mean age of 37.19 and 48.88 years, respectively, were evaluated. The results showed that 63% were born in the state of Amapá and 61% are married. Regarding educational level, 43% have completed high school. As for work, 54% are employed. Among the 76% who work have a journey 20-40 hours weekly. On family income, 78% receive 1-3 times the minimum wage. Regarding the time of physical activities, they practiced on average 37.3 months and accompanied his majority, with 52% of respondents. The frequency of physical activity is on average 4.85 times per week and 93 minutes per session. Regarding objectives, 48% is intended to improve health. From the data on the profile of practitioners from academia to the square, it is possible to suggest more effective public policies for health prevention programs, based on physical activity, as well as encouraging the practice and as a way to meet the need a population with low income.
Keywords: Profile - physical activity - square.